Analysis and performance evaluation of axial flux permanent magnet motors - Dwivedi A.; Singh S.K.; Srivastava R.K. (My University, 2025)
A two-dimensional analytical method for the performance evaluation of axial flux permanent magnet (AFPM) machine has been presented in this paper. The method computes the electromagnetic torque, magnetic field distribution, cogging torque and back EMF of the machine using quasi-3D modeling. Fourier Transform is used for the solution of Maxwell's equations in different regions of the AFPM machine. A surface mounted AFPM motor is tested and the experimental results validate the proposed method. © 2016 IEEE.